HUBUNGAN SPIRITUAL WELL-BEING DAN PSYCHOLOGICAL WELL-BEING DENGAN RESILIENSI PASIEN HEMODIALISIS - Umi Setianingsih; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (Jurnal Medicare, 2026)
Patients with chronic kidney disease undergoing long-term hemodialysis are exposed to sustained physical, psychological, and spiritual stressors that may adversely affect their adaptive capacity or resilience, thereby necessitating a comprehensive care approach that extends beyond clinical management to encompass holistic well-being. This cross-sectional correlational study examined the association between spiritual well-being, psychological well-being, and resilience among 99 hemodialysis patients at RSI Sultan Agung Semarang selected through purposive sampling. Data were collected using the FACIT-Sp-12, Psychological Well-Being Scale, and Connor–Davidson Resilience Scale and analyzed using the Gamma test. Most participants demonstrated moderate spiritual well-being (60.6%), high psychological well-being (88.9%), and good resilience (75.8%). Significant positive associations were found between spiritual well-being and resilience (r = 0.919; p = 0.001) and between psychological well-being and resilience (r = 0.903; p = 0.001). These results suggest that spiritual and psychological well-being are key factors associated with resilience in patients undergoing hemodialysis, underscoring the importance of integrating spiritual and psychological interventions into nursing care to strengthen patients’ ability to cope with long-term treatment.